2018
DOI: 10.1038/s41598-018-34186-0
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β inhibition attenuates LPS-induced IL-6 expression in porcine adipocytes

Abstract: IL-6 is not only a proinflammatory cytokine associated with inflammatory responses but also a regulator on the energy and glucose metabolism in adipose tissue. Glycogen synthase kinase 3β (GSK3β) has fundamental roles in the regulation of pro- and anti-inflammatory cytokines production. However, the regulatory role for GSK3β in the pig inflammatory response in adipocytes remains unknown. We show here that SB216763 and LPS increased the phosphorylation of GSK3β (Ser9), and decreased the phosphorylation of GS (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Similar to our results, LPS up-regulated the expression of CCL2 and CCL8 in human adipocytes (44), and CCL2 in mouse adipocytes (15). Of note, although microarray results showed down-regulation of IL8 and no effect on IL6 expression after LPS stimulation (Figure 5), we checked the expression of both cytokines by qRT-PCR because of their up-regulation is well-reported in LPS responses of human (44), mouse (15), and pig (45) adipocytes. Although it was statistically insignificant, but both IL6 and IL8 expression showed an upward trend after LPS stimulation (Figure 7C).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, LPS up-regulated the expression of CCL2 and CCL8 in human adipocytes (44), and CCL2 in mouse adipocytes (15). Of note, although microarray results showed down-regulation of IL8 and no effect on IL6 expression after LPS stimulation (Figure 5), we checked the expression of both cytokines by qRT-PCR because of their up-regulation is well-reported in LPS responses of human (44), mouse (15), and pig (45) adipocytes. Although it was statistically insignificant, but both IL6 and IL8 expression showed an upward trend after LPS stimulation (Figure 7C).…”
Section: Discussionmentioning
confidence: 99%
“…LPS can cause severe inflammatory reaction and promote the expression of pro‐inflammatory mediators (Lopes, 2017) . Wang L et al found that LPS can significantly promote the expression of IL‐6, and inhibition of IL‐6 expression significantly inhibited LPS‐induced inflammatory response (Wang, Li, & Wang, 2018). Bailly S et al showed that LPS can significantly activate the expression of IL‐1β in human monocytes (Bailly et al., 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that IL-6 is not only a pro-inflammatory cytokine, but also regulates energy and glucose metabolism. A group of scientists [15] in experiments with pigs found that blocking IL-6 transsignaling can prevent the recruitment of macrophages from adipose tissue with a high fat content, but does not induce body weight gain and improved insulin resistance. "Overexpression of the IL-6 gene induces a significantly reduced body weight, improves insulin sensitivity, and increases the mRNA level of lipolysis genes.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the infection and inflammation by their ability to increase pro-inflammatory cytokines, chemokines and adhesion molecules play a key role in the pathophysiology of insulin resistance and type 2 diabetes. Studies carried out by the group of authors [13,15] have shown that GSK-3 plays a central role in the regulating such inflammation. In particular, it was found that inhibition of GSK3α/β suppresses inflammation in response to various stimuli such as TNF-α, IL-1β and LPS in vitro".…”
Section: Introductionmentioning
confidence: 99%